PENINGKATAN DESAIN MANAJEMEN SUMBER DAYA MANUSIA BERBASIS MADRASAH DINIYAH TAKMILIYAH: (Studi Kasus di MDTA Al-Hidayah Srimulyo Dampit) - Muhammad Zainul Anwar (Pascasarjana Universitas Al-Qolam Malang, 2025)
This study examines the enhancement of Human Resource Management (HRM) design at Madrasah Diniyah Takmiliyah Awaliyah (MDTA). A case study was conducted at MDTA Al-Hidayah Srimulyo Dampit, where several HRM-related issues were identified, including the low frequency and effectiveness of meetings, the absence of a clear and fair salary system, a decline in student enrollment, a lack of teacher discipline and motivation, and limited parental involvement. The research employed a Participatory Action Research (PAR) approach to facilitate the restructuring of the HRM system at MDTA Al-Hidayah. The findings indicate efforts toward transforming the HRM design, particularly in managerial functions (planning, organizing, directing, and controlling), compensation budgeting, and the integration of human resources through improved communication and collaboration. This study is expected to contribute to the development of Islamic education management knowledge, particularly in the context of Madrasah Diniyah Takmiliyah, and to offer a practical model for improving HRM in non-formal Islamic educational institutions. Keywords: Human Resource Management, Madrasah Diniyah Takmiliyah